(untitled) (Damascus University Journal of arts and humanities sciences, 2023)
The concept of land use in geography holds great importance, as it crystallizes images of human interaction with the land, and the process of surveying land use was the head of the ladder that pushed geography to the ranks of applied sciences, tracking its changes over time, studying the factors affecting the use of the land, and contributing to the development of plans aimed at using the land in an optimal manner that preserves its resources and ensures its sustainability. The research aimed to shed light on the issue of land use changes over time and the need to preserve, maintain and manage natural resources in an optimal way, by using quantitative methods to track changes in land use patterns in the studied area over a period of forty years. The research came to the conclusion that: the decline in the areas of arable land and the deterioration of pastures and forests in Homs governorate as a result of the acceleration of urban sprawl, pressure on natural resources and encroachment on ecosystems. The research recommended planning based on scientific foundations to prevent the wrong use of the land, and to promote its use in a way that meets the growing needs of society in housing and production, and to work to consolidate the concept of environmental awareness in order to achieve the ultimate goal, which is the optimal use of land in the Syrian Arab Republic.